2011
DOI: 10.1186/1471-2458-11-664
|View full text |Cite
|
Sign up to set email alerts
|

The Big Drink Debate: perceptions of the impact of price on alcohol consumption from a large scale cross-sectional convenience survey in north west England

Abstract: BackgroundA large-scale survey was conducted in 2008 in north west England, a region with high levels of alcohol-related harm, during a regional 'Big Drink Debate' campaign. The aim of this paper is to explore perceptions of how alcohol consumption would change if alcohol prices were to increase or decrease.MethodsA convenience survey of residents (≥ 18 years) of north west England measured demographics, income, alcohol consumption in previous week, and opinions on drinking behaviour under two pricing conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 31 publications
4
21
0
Order By: Relevance
“…The mean elasticity by across the studies included in the review was -0,28. In contrast, several authors reported that heavy drinkers may be unresponsive to price, or, at list, less responsive than moderate drinkers (Cook et al, 2011). The results from present analysis suggest a close aggregate-level link between vodka affordability and alcohol-related mortality and support the idea that low affordability of alcohol is associated with reduction in binge drinking and that the effect of pricing policy would be greater on harmful drinkers.…”
Section: Discussionsupporting
confidence: 59%
“…The mean elasticity by across the studies included in the review was -0,28. In contrast, several authors reported that heavy drinkers may be unresponsive to price, or, at list, less responsive than moderate drinkers (Cook et al, 2011). The results from present analysis suggest a close aggregate-level link between vodka affordability and alcohol-related mortality and support the idea that low affordability of alcohol is associated with reduction in binge drinking and that the effect of pricing policy would be greater on harmful drinkers.…”
Section: Discussionsupporting
confidence: 59%
“…Although young adults have been demonstrated as a group particularly sensitive to price (Dhalwani, 2011; Lockhart, Beck, & Summons 1993) how price sensitivity might emerge within the enactment of young adulthood (in which peer belonging becomes central) and the potential for variation therein is less understood within alcohol pricing research. A study in England (Cook et al., 2011) of consumers of all ages found the 18–24 year old subgroup more likely to decrease consumption in light of hypothesized price increases (30% compared to 22% of the entire all age sample), yet other evidence points to a contextual influence on the relationship between price and consumption. For example, Purshouse et al.…”
Section: Young Adulthood As a Context Of Alcohol Decision Makingmentioning
confidence: 99%
“…Although attempts to understand the price sensitivities of different subgroups within a population have not been absent from the evidence base for MUP, analyses of variations in responses (often expressed as consumer ‘elasticities’) have tended to operationalize ‘heterogeneity’ in terms of the individual characteristics of drinkers such as their sex and age (Cook et al., 2011; Herttua, Makela, & Martikainen, 2008; Heeb, Gmel, Zurbrugg, Kuo, & Rehm, 2003) or type of drinker, such as whether moderate or heavy consumers (Ayyagari, Deb, Fletcher, Gallo, & Sindelar, 2011; Cook et al., 2011). However, there is less evidence relating to the context in which the drinking takes place as a salient feature of cultural heterogeneity; the different meanings, values and practices around alcohol that operate in the contexts different groups drink.…”
Section: Minimum Unit Pricing As a Policy Response Formulated Within mentioning
confidence: 99%
“…Of key importance is the ability to 'trade down' to cheaper brands and types of alcohol, and should that option be removed, following, for example, the introduction of MUP, then their ability to obtain alcohol, particularly in large quantities, will be severely restricted. Cook et al (2011) reported that even if prices are increased, drinkers can avoid reducing their drinking through sacrificing other purchases or necessities. Our findings are in agreement, but for some drinkers there is currently the fallback of cheaper alcohol.…”
Section: Discussionmentioning
confidence: 99%